Teaching English to Linguistically Diverse Students from Migration Backgrounds: From Deficit Perspectives to Pockets of Possibility - Elizabeth J. Erling; Anouschka Foltz; Felicitas Siwik; Michael Brummer (Languages, 2022)
This article reports on an interview study with six secondary school LX English teachers working in a part of Austria where there is an above-average number of residents–and thus also students–who are multilingual and come from migration backgrounds. It attempts to extend research on deficit perspectives of multilingual learners from migration backgrounds to the area of LX English learning and to provide insights into a language learning context that is underrepresented in international applied linguistics research, which has tended to focus on elite language learning. The article explores teachers’ perceptions of teaching English in this context. We hypothesized that teachers would hold negative beliefs about their students’ multilingual backgrounds and practices. The typological analysis of teachers’ interview data revealed that teachers did hold some dominant deficit perspectives about their students’ multilingualism and language learning; however, it also suggests that teachers are taking on the rudiments of a translanguaging stance that values multilingual practice. The article thus closes by considering how possibility perspectives can be harnessed and extended to foster students’ multilingual and multicultural development, with particular regard to LX English language learning.